Rio Madeira HVDC System: Commissioning of the Ground Electrode for Bipole 2 at Porto Velho - Paulo Freire; Jairo Kalife; Gil Oliveira (Applied Sciences, 2022)
The original ground electrode of the Madeira River HVDC transmission system, bipole 2, was discarded due to the risk of saturation of the transformers in the Converter Substation of Porto Velho, located 15 km away, during the monopolar operation with ground return. After an extensive geophysical survey, a new site was selected, 40 km from the converter substation. For the confirmation of the new site, it was built in the central area of the site, a single-well 47 m deep test electrode, interconnected to the original 15 km electrode line by an additional 40 km long temporary line. A new electrode was then designed. This paper summarizes the test electrode procedure and the activities developed for the new electrode commissioning after its construction, which can be divided into two phases–pre-commissioning and commissioning. The electrode pre-commissioning was performed before its energization for the evaluation of the integrity of its components. The commissioning tests started with electrode energization, employing the electrode line, and an unbalanced bipole operation, which allowed the evaluation of its electrical performance. However, the main objective of the paper is the evaluation of the electrode resistance, which is an essential HVDC electrode parameter.